ANALISIS PERBANDINGAN MODEL PROPAGASI PADA KOMUNIKASI SELULER 5G WILAYAH JAKARTA UTARA - zaki, Achmad zaidan; Purnawan, Peby Wahyu; Fath, Nifty (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2024)
In the realm of wireless communication, the choice of frequency and propagation model significantly influences signal propagation characteristics. This study delves into the comparative analysis of propagation models in 5G cellular communication, specifically focusing on the North Jakarta region. By employing the NYUSIM tool alongside 3GPP, Walfish-Ikegami, and ITU-R models, simulations were conducted at frequencies of 28 GHz and 3.5 GHz. The findings reveal a positive correlation between transmission distance and both Line-of-Sight (LOS) and Non-Line-of-Sight (NLOS) losses. As distance increases, LOS and NLOS values tend to elevate. At 28 GHz with the Omni antenna, LOS at 200 meters reaches 115.00 dB, while NLOS is 130.04 dB. However, using the Direc antenna at the same frequency and distance, LOS increases to 122.80 dB, and NLOS to 137.50 dB. Furthermore, frequency variation affects simulation outcomes, with 3.5 GHz displaying a broader range of Path Loss values (3.66 dB to 22.82 dB) compared to 28 GHz (4.40 dB to 23.53 dB). Consequently, the study underscores the critical role of frequency selection in determining signal loss levels and emphasizes the necessity of understanding frequency characteristics for efficient and reliable wireless communication network design.